Method and procedure of pile load test in PTD 182919, Bukit lndah, Iskandar Puteri, Johor / Nur Erisha Emalin Alwi - Alwi, Nur Erisha Emalin (Universiti Teknologi MARA, Perak, 2019)
Piles are designed to transfer any dead or live load of superstructure to the deepest state of soil. Reinforcement concrete piles or RC piles are one of the common piles use and design by many analyses and using many formulas. But due to the uncertainties of problems such as soil behaviour, these piles need to be tested using several tests such as maintain load test to identify the strength of the pile. A case study of maintain load test of RC piles is conducted and the data and result are collected through settlement curves. The main objective of this case study is to determine the method construction for maintaining load test, time taken to complete the test and to determine the hazard occur during the test conducted. The findings show a method of test pile is constructed and been observed the load.